2000
DOI: 10.1128/iai.68.8.4378-4383.2000
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Urease Suppresses Bactericidal Activity of Peroxynitrite via Carbon Dioxide Production

Abstract: Helicobacter pylori can produce a persistent infection in the human stomach, where chronic and active inflammation, including the infiltration of phagocytes such as neutrophils and monocytes, is induced. H. pylori may have a defense system against the antimicrobial actions of phagocytes. We studied the defense mechanism of H. pylori against host-derived peroxynitrite (ONOO ؊ ), a bactericidal metabolite of nitric oxide, focusing on the role of H. pylori urease, which produces CO 2 and NH 3 from urea and is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
84
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 54 publications
0
84
0
Order By: Relevance
“…Enzymic degradation of urea by urease results in the production of ammonia and bicarbonate, and both reaction products are thought to play an important part in bacterial pathogenesis. Ammonia serves as nitrogen source and may function in acid resistance (Burne & Chen, 2000;Scott et al, 2002;Williams et al, 1996), whereas bicarbonate may also function in acid resistance as well as in modulating the immune system of the host (Kuwahara et al, 2000;Marcus et al, 2005). Expression of urease in bacteria is controlled by different stimuli, such as urea availability, environmental pH, nitrogen status of the cell, or growth phase (Burne & Chen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymic degradation of urea by urease results in the production of ammonia and bicarbonate, and both reaction products are thought to play an important part in bacterial pathogenesis. Ammonia serves as nitrogen source and may function in acid resistance (Burne & Chen, 2000;Scott et al, 2002;Williams et al, 1996), whereas bicarbonate may also function in acid resistance as well as in modulating the immune system of the host (Kuwahara et al, 2000;Marcus et al, 2005). Expression of urease in bacteria is controlled by different stimuli, such as urea availability, environmental pH, nitrogen status of the cell, or growth phase (Burne & Chen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that H. pylori induces iNOS and NO production in macrophages (6,(21)(22)(23)47). NO can kill the bacterium in vitro (6,22,30), but H. pylori survives in the human stomach despite detection of iNOS in the infected gastric mucosa (19). It is important to note that even when H. pylori is separated from the mucosal macrophages, NO itself is freely diffusible and can be detected systemically under conditions of infection or other forms of stress where iNOS is upregulated (for a review, see reference 17).…”
mentioning
confidence: 99%
“…H. pylori can induce iNOS and other innate immune response genes in macrophages even when separated by filter supports or when water extracts are used (6). Although H. pylori-induced NO production can kill the bacterium in vitro (7,9), it survives in the stomach, despite detection of iNOS in infected gastric mucosa (10).…”
mentioning
confidence: 99%